Interactive Video Media and Podcast Model to Improve Motivation and Critical Thinking class IX Students SMPN 1 Purwanegara - Sriyanto Sriyanto; Fajriyatun Fajriyatun (LANGGAM: International Journal of Social Science Education, Art and Culture, 2024)
In addition to having teaching skills in delivering learning content, teachers must also have knowledge and skills in developing technology-based learning resources for learner-centered learning. The utilization of information and communication technology that contributes to preparing 21st century learning is video-based learning media. Many research results state that the use of video media and podcast models can increase learning motivation and critical thinking of students. Critical thinking skills need to be possessed by students to equip them to live in the 21st century. Initial observation data, students who have high and very high learning motivation are only 26.09% and their critical thinking skills are only 56.32% of students with high and very high categories. The purpose of this study is to describe the results of learning innovation research in the form of using interactive video media and podcast models to increase learning motivation and critical thinking of class IX students of SMPN 1 Purwanegara. The method used was Classroom Action Research (PTK) which was conducted at SMP Negeri 1 Purwanegara. The population was all ninth grade students of SMP Negeri 1 Purwanegara which amounted to 272 students. The sample in this study were students of class IX F. Learning media in the form of interactive videos and podcast models used in this learning research were made to familiarize and train students to think critically and have high learning motivation. The results of research activities are that students experience an increase in their learning motivation of 91.31% in the high and very high categories. Students have been able to follow the learning process by using interactive video media and podcast models very well. Based on the results of the research conducted, it can be concluded that the learning process using interactive learning videos and podcast models can increase students' learning motivation. Interactive video media and podcast models can be an alternative learning innovation that makes students more actively involved in learning activities and increases students' learning motivation.